EDUKASI STRETCHING METODE PNF BAGI ATLET DISABILITAS INTELEKTUAL SPECIAL OLYMPICS INDONESIA DKI JAKARTA - Slamet Sukriadi; Muhamad Arif; Bazuri Fadillah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2022)
Abstract Coaching for Intellectual athletes with disabilities Special Olympics DKI Jakarta aims to improve sports skills and also has an impact on the ability of physical components including flexibility so that athletes are not prone to injury from the training process carried out. However, the obstacle in the coaching is that not all coaches and parents understand and consider the importance of stretching exercises, especially exercises with the PNF method that have not been carried out optimally. Based on the situation analysis, the partner problem education that will be carried out in this community service is PNF method stretching education for athletes with Intellectual Disabilities Special Olympics Indonesia DKI Jakarta. By providing this education, it can help coaches and parents to create good and useful stretching exercise programs for athletes. In this PKM activity, the main priority will be to provide education about stretching the PNF (Propioceptive Neuromuscular Facilitation) method. The method in this activity is education that is in accordance with the analysis of the situation and the needs of the target. This Community Service Implementation Program was carried out in 5 Special Olympics Indonesia Special Olympics Development Centers DKI Jakarta during the 1 year process. Abstrak Pembinaan Sepanjang Tahun bagi atlet Inteletual disabilitas Special Olympics DKI Jakarta bertujuan untuk meningkatkan keterampilan cabang olahraga dan juga berdampak pada kemampuan komponen fisik termasuk fleksibilitas sehingga, atlet tidak rentan cidera dari proses latihan yang dilakukan. Namun yang menjadi kendala dalam pembinaan tersebut adalah tidak semua pelatih dan orang tua mengerti dan faham serta menganggap penting latihan peregangan terutama latihan dengan metode PNF yang belum dilaksanakan secara optimal. Berdasarkan analisis situasi maka Edukasi permasalahan mitra yang akan di laksanakan dalam pengabdian masyarakat ini adalah edukasi stretching metode PNF bagi atlet Disabilitas Intelektual Special Olympics Indonesia DKI Jakarta. Dengan diberikannya edukasi ini dapat membantu Pelatih dan orang tua, untuk membuat program latihan peregangan (stretching) yang baik dan bermanfaat untuk atlet. Dalam kegiatan pengabdian ini yang akan di jadikan prioritas utama adalah memberikan Edukasi tentang stretching metode PNF (Propioceptive Neuromuscular Facilitation). Metode yang dipakai dalam kegiatan ini adalah edukasi yang disesuaikan dengan analisis situasi dan kebutuhan khalayak sasaran stategis. Program Pelaksanaan Pengabdian kepada Masyarakat ini di laksanakan di 5 Wilayah Sentra Pembinaan Special Olympics Indonesia DKI Jakarta, dengan proses 1 tahun